Learning, neural plasticity and sensitive periods: implications for language acquisition, music training and transfer across the lifespan - White, Erin J.; Hutka, Stefanie A.; Williams, Lynne J.; Moreno, Sylvain (Frontiers in Systems Neuroscience, 2013)
Sensitive periods in human development have often been proposed to explain age-related differences in the attainment of a number of skills, such as a second language and musical expertise. It is difficult to reconcile the negative consequence this traditional view entails for learning after a sensitive period with our current understanding of the brain’s ability for experience-dependent plasticity across the lifespan. What is needed is a better understanding of the mechanisms underlying auditory learning and plasticity at different points in development. Drawing on research in language development and music training, this review examines not only what we learn and when we learn it, but also how learning occurs at different ages. First, we discuss differences in the mechanism of learning and plasticity during and after a sensitive period by examining how language exposure versus training forms language-specific phonetic representations in infants and adult second language learners, respectively. Second, we examine the impact of musical training that begins at different ages on behavioural and neural indices of auditory and motor processing as well as sensorimotor integration. Third, we examine the extent to which childhood training in one auditory domain can enhance processing in another domain via the transfer of learning between shared neuro-cognitive systems. Specifically, we review evidence for a potential bi-directional transfer of skills between music and language by examining how speaking a tonal language may enhance music processing and, conversely, how early music training can enhance language processing. We conclude with a discussion of the role of attention in auditory learning for learning during and after sensitive periods and outline avenues of future research.